Electromagnetic shielding performance of three-dimensional woven fabrics with copper-based hybrid yarn in X-band frequency range. (October 2019) - Pandey, Dharmendra Nath; Basu, Arindam; Kumar, Pramod; Baskey, Himangshu B
This study involves a comprehensive evaluation of electromagnetic shielding characteristics of multilayer three-dimensional conductive fabrics by using cotton/copper wrapped hybrid yarn in X band frequency range. Five, three-dimensional fabrics with different structural configuration, such as orthogonal, angle interlock, cellular spacer, multi-tubular spacer, and contour were produced. Three different series of all five structures was also developed using pure cotton fabric, conductive hybrid yarn in weft and one-third hybrid yarn and two-third cotton yarn in warp Also, the effect of vertical and horizontal polarization of electromagnetic waves on electromagnetic shielding effectiveness was studied. The comparative analysis of reflectance transmittance and absorption behavior was also undertaken. The results indicate that pure cotton fabric (A series) does not have electromagnetic shielding capabilities. The difference between the electromagnetic shielding effectiveness values in vertical and horizontal planes of fabrics, having conductive hybrid yarn in weft direction (B series), showed significantly better results on the vertical plane in comparison to that on the horizontal plane. Fabric containing conductive hybrid yarn in both warp and weft (C series) exhibits consistent electromagnetic shielding effectiveness in both the planes. It is worth mentioning that the structural configuration in all five three-dimensional fabrics in B and C series has shown differential trends of electromagnetic shielding effectiveness in terms of reflectance, transmittance and absorption behavior. They are also found to be statistically significant. Finally, it is concluded that the conductive 3-D multilayer system develops special protective capabilities, mostly due to its larger surface area.